Analysis of Material Supply Chain Risk Weight Using Severity Index Method - Debataraja, Lisherly; Purba, Marsedes; Amrizal; Budianto, Gallio; Sinaga, Naga Raya (LPPM Politeknik Aceh Selatan, 2024)
Material delay is a vital problem in the completion of construction work, this is closely related to the understanding of the flow of material supply. So it takes risk weight analysis from the internal side (supply, control, process, demand) and external (disaster factor). This study began with a literature study to obtain a list of risks, then data collection using a questionnaire method to 50 respondents who are experts in construction material procurement. Furthermore, a risk analysis was carried out using the severity index method. From this analysis, the average risk from the supply side was 16.40%, the control risk was 16.29%, the process risk was 11%, the demand risk was 16.11% and the disaster risk was 13.79%. There are two most dominant delay risks, namely material delays due to constraints in the factory process to material limitations at the supplier and late payments from the main contractor to the subcontractor so that material orders are late.